EU Refugee Resettlement: Key Challenges of Expanding the Practice into New Member States - Jakulevičienė Lyra; Bileišis Mantas (Baltic Journal of Law & Politics, 2016)
Refugee resettlement is not new to EU member states. But the EU only accounts for about 10 percent of resettlements globally. Before the 2015 European Council decisions to relocate about 160,000 persons from Italy and Greece only half of EU Member States participated in resettlement programs. Relocation of refugees has emerged as a new form of resettlement as an EU reaction to the growing refugee influx. It is likely to become a permanent part of Common European Asylum Policy. The refugee emergency has intensified discussions about the application of the solidarity principle to pressure member states not yet engaged in relocation to contribute to the joint efforts of the EU. But this has created serious political controversy in many of the new (eastern) member states.